Anxielytic Effects of Portulaca oleracea Aqueous Extracts in Mice - H Miladi-Gorgi; AA Vafaei; A Rashidypour; AA Taherian; M Jarrahi; M Emami abarghoii; H Sadeghi (Institue of Medicinal Plants, ACECR, 2006)
Background: Portulaca oleracea (PO) overgrows in different parts of Iran. In previous studies, a 10% hydroalcoholic extract of the PO aerial parts (leaf and stem) showed anticeptive and anticonvulsive activity in rats. Objective: This study was designed to evaluate anxielytic effects in different doses of the aqueous decoction extracts of PO seed. Methods: In this study, forty male mice (25-30 gr) were used in a model Elevated Plus Maze (EPM). Different doses of the extract (25, 50, 75 mg/kg) were injected intraperitoneally (IP) to three separated test groups and normal saline (10ml/kg, IP) was injected to one control group, intraperitoneally. For increasing their activity, animals were put inside a black box for 5 min. Then they were transferred to the elevated plus maze and evaluated for their anxiety reaction, including number and percent of time spent in open arm. Results: Results indicated that injection of the extract in three doses of PO reduced anxiety reaction in test groups, compared with the control group which had higher number of entrances and spent more time in open arm (P=0.000). Conclusion: It is suggested that the aqueous extract of PO plays an important role in fear and anxiety reactions and that the anxielytic effects of PO is not related to the dosage of use.